Molecular Characterization of Selected Local and Exotic Cattle Using RAPD Marker - M. Mahfuza Khatun; Khondoker Moazzem Hossain; S. M. Mahbubur Rahman (Asian-Australasian Journal of Animal Sciences, 2012)
In order to develop specific genetic markers and determine the genetic diversity of Bangladeshi native cattle (Pabna, Red Chittagong) and exotic breeds (Sahiwal), randomly amplified polymorphic DNA (RAPD) analysis was performed using 12 primers. Genomic DNA was extracted from 20 cattle (local and exotic) blood samples and extracted DNA was observed by gel electrophoresis. Among the random primers three were matched and found to be polymorphic. Genetic relations between cattle’s were determined by RAPD polymorphisms from a total of 66.67%. Statistical analysis of the data, estimating the genetic distances between cattle and sketching the cluster trees were estimated by using MEGA 5.05 software. Comparatively highest genetic distance (0.834) was found between RCC-82 and SL-623. The lowest genetic distance (0.031) was observed between M-1222 and M-5730. The genetic diversity of Red Chittagong and Sahiwal cattle was relatively higher for a prescribed breed. Adequate diversity in performance and adaptability can be exploited from the study results for actual improvement accruing to conservation and development of indigenous cattle resources.